COMMODIFICATION OF TEKTEKAN CALONGARANG AT BATURITI, KERAMBITAN, TABANAN - Sariada, I Ketut; Wirawan, AA Bagus; Kumbara, Anak Agung Ngurah Anom; Ruastiti, Ni Made (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2016)
Tektekan Calonarang is a Calonarang drama dance which is performed for a new model of tourism, and is accompanied with what is referred to gamelan tektekan. In general, the Balinese people disagree that a sacred cultural element is performed for tourism. However, those living at Baturiti Village support the commodified Tektekan Calongarang in which what are referred to as sacred barong and rangda are performed. This has led to many questions as such a performing art contrasts with the Balinese people’s attitude in general. The problems of the present study are formulated as follows: why the people living at Baturiti Village, Kerambitan, Tabanan, support the commodified Tektekan Calongarang using the sacred rangda and barong; what was such a commodification like; what was its implication on those who were involved in it, society, and such a performance itself. This present study is a qualitative one in which a number of related critical theories were used such as the theory of deconstruction proposed Jacques Derrida, the theory of social practice proposed by Pierre Bourdieu, and the theory of power/knowledge proposed by Michael Foucault. The result of the study showed that the commodified Tektekan Calonarang in which the sacred barong and rangda were used was performed in the forms of a procession and the Tektekan Calonarang performance. The market ideology, the developmental ideology, the religious ideology, and the conservation ideology inspired the commodified Tektekan Calonarang which involved the sacred barong and rangda performed for tourism. Such a commodification increased the income of those involving in such a performance and the local people (multiplier effects), the perpetuity of the magical strength of such barong and rangda, the market/tourism interest, and strengthened the local people’s social solidarity. The novelty of the present study was that there was no degradation of sacredness although the sacred rangda and barong were commodified for tourism. The reason is that every time such a performance was performed, a ritual was performed to purify such barong and rangda contextually.